Using a continuous improvement tool to improve workers' well-being and productivity - A case study in a piglet cutting workstation - Brito, Marlene (2018)
Nowadays there is an increasing concern for well- being. However, workers continue to suffer from musculoskeletal disorders, which are one of the most widely recognized types of occupational disease. Meat cutters face higher risks of injury and musculoskeletal problems than most other occupational groups due to repetition, force, static posture, work organization, and lack of recovery time. The aim of this paper is to use a continuous improvement audit tool to analyze the current situation of a piglet cutting workstation and then identify measures to improve it, considering productivity and workers’ well-being.